Where value hides : - Jackson, Stuart E. (John Wiley, 2007)
Where Value Hides is a fresh read on a topic much discussed but rarely understood in its finer points: market share and its impact on value creation. All company leaders strive for greater market share, but are they asking the question, Will higher share really benefit the organization in the long run? Judging from the examples Jackson sites, I would say that far too few do in fact ask this question and fewer still answer it with any degree of analysis and strategic clarity.